Auditory discrimination in aging bilinguals vs. monolinguals with and without hearing loss - Hisagi, Miwako; Barragan, Beatriz; Diaz, Arlene; White, Kai; Winter, Margaret (Frontiers in Aging, 2024)
Demands for effective assessments of speech perception specific to the aging brain are increasing, as the impacts of hearing loss on an individual's functional health, socialization, and cognition have become more widely recognized. Understanding the mechanisms behind the optimal function of the aging brain in relation to speech and language is challenging, especially in the bilingual population where the language learning and language interference processes could be mistaken for perceptual difficulty. Age-related presbycusis is unavoidable, and the contributions of this sensorineural hearing loss (SNHL) process on impaired speech recognition are not completely understood. This lack of understanding of the effects of aging and bilingual language competency on speech perception can act as a barrier to successful auditory rehabilitation. The present study investigated the effects of aging on vowel sound discrimination in adult listeners (age 50+) with the following characteristics: American English (AE) monolinguals with normal hearing, simultaneous or early sequential Spanish-English (SE) bilinguals with normal hearing, and AE monolinguals with SNHL (AE-SNHL). The goal was to identify the differences in vowel sound discrimination performance between the monolingual and bilingual aging populations to guide future language assessments and intervention processes. English vowel discrimination was assessed using an AXB discrimination task in quiet and using the Quick Speech in Noise (QuickSIN) test. SE bilinguals were outperformed by AE and AE-SNHL monolinguals, suggesting SE bilinguals primarily use their L1 acoustic properties to discriminate speech segments. No significant difference was found in QuickSIN performance between the bilingual and the monolingual groups, but there was a significant difference between AE and AE-SNHL. In conclusion, vowel discrimination was affected by interference with the native language, while performance in the noise condition was affected by hearing loss. The results of this study contribute to our understanding of the age-related speech processing deficits from three different aging groups regarding the cognitive control system.